Marketing Competency, Marketing Innovation, and Sustainable Competitive Advantage of Small and Medium Enterprises (SMEs): A Study on Eucalyptus Oil SMEs in Buru District - Lestari, Feni Ayu; Rufaidah, Popy (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The research seeks to ascertain the influence of marketing proficiency and innovative marketing strategies on enduring competitive advantage inside of small enterprises and medium enterprises (SMEs) of eucalyptus oil in Buru Regency. data was collected via a questionnaire administered to 60 populations of eucalyptus oil entrepreneurs in Buru Regency. inside of this research, the explanatory variable of marketing competency uses two dimensions, namely capabilities and resources. Then for the independent variable of marketing innovation utilizing four dimensions, namely novelty in offerings, pricing strategies, sales channel advancements, and marketing communication breakthroughs. While for the dependent variable of sustainable competitive advantage, the dimensions used are product innovation advantage, managerial capabilities, and competitive resilience. These dimensions are adopted by previous studies by relevant variables constituting the primary emphasis of the investigation. Verification of hypotheses, assessment of validity, and evaluation of reliability were conducted utilising PLS-SEM as the analytical approach. The outcomes of the research that have been presented show that marketing competency exhibits no substantial influence on enduring competitive advantage, whereas marketing innovation demonstrates a favourable and notable influence. This outcome states that innovation strategies increase the competitiveness of SMEs, especially in products According to superior commodities.